2022
DOI: 10.1002/hep4.1974
|View full text |Cite
|
Sign up to set email alerts
|

Chronic hepatitis B virus infection and the risk of hepatocellular carcinoma by age and country of origin in people living in Sweden: A national register study

Abstract: Chronic hepatitis B virus (HBV) infection is a major risk factor for hepatocellular carcinoma (HCC), and surveillance is recommended for patients without cirrhosis when risk exceeds an incidence rate (IR) of 0.2%. Populations in Asia and sub‐Saharan Africa have been associated with HCC at younger ages, but the risk after immigration to Western countries should be investigated. The aim of this study was to study HCC by age and country of origin in people with chronic HBV infection in Sweden. Through national re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 26 publications
(42 reference statements)
1
14
0
Order By: Relevance
“…Asian individuals with CHB also have a higher incidence of HCC and earlier occurrence. 33 In this study, Asian participants had the highest prevalence of HBeAg and the highest percentage meeting treatment criteria and were most likely to initiate treatment; however, treatment initiation among those eligible was comparable to that of African American or Black and White participants, and clinical outcomes including HCC were also similar.…”
Section: Discussionmentioning
confidence: 61%
“…Asian individuals with CHB also have a higher incidence of HCC and earlier occurrence. 33 In this study, Asian participants had the highest prevalence of HBeAg and the highest percentage meeting treatment criteria and were most likely to initiate treatment; however, treatment initiation among those eligible was comparable to that of African American or Black and White participants, and clinical outcomes including HCC were also similar.…”
Section: Discussionmentioning
confidence: 61%
“…Although the World Health Organization recommended universal vaccination with the hepatitis B vaccine for children in 1995, Denmark, Finland, Iceland, Ireland, the Netherlands, Norway, Sweden, and the UK adopted a selective vaccination strategy for high-risk groups, which was controversial at that time [20,21] . These countries originally had a low prevalence of hepatitis B infection, which may be related to the in ux of immigrants from other countries and regions [22] . Our results further illustrate the necessity for timely hepatitis B vaccination in all children.…”
Section: Discussionmentioning
confidence: 99%
“… 6 Recent studies reported that the risk of HCC differs extensively across etiologies, age, and sex in patients with cirrhosis. 25 , 26 Thus, HCC surveillance in elderly patients with HBV or HCV-related LC is imperative. NSSs, including APRI, GPR, FIB-4, is a risk factor for HCC development in patients with CHB and fatty liver disease.…”
Section: Discussionmentioning
confidence: 99%